Learning Traditional Denok Dance With Kinect Game - Dominikus Reynard Darmawan; Erdhi Widyarto Nugroho; Ridwan Sanjaya (Soegijapranata Catholic University, 2021)
Nowadays, culture exchange is so much easier, with the foreign culture walk in to Indonesia, our traditional culture start to be forgotten, one of them is our traditional dance. And also, studying our native culture is considered something outdated. That why its needed a new media to make our traditional culture more modern so not become forgotten. One of the media which can be used is a game and a technology called kinect, with both of it, can be made a simulation game of our traditional dance, so it can be a media for introducing our traditional dance or help to train the dancer.